An investigation on shear banding and crystallographic texture of Ag–Cu alloys deformed by high-pressure torsion. (February 2019) - Ghosh, P; Kormout, KS; Todt, J; Lienert, U; Keckes, J; Pippan, R
Ag–Cu alloys of two different initial microstructures—a cast eutectic alloy (AgCu-E) and an equivolume Ag–Cu powder mixture (AgCu-P)—were deformed by high-pressure torsion. The codeformation of Ag and Cu grains led to uniform refinement and a nanolamellar microstructure for both alloys. However, the lamellar structure in AgCu-P alloys was broken at intermediate shear strains (γ > 150) by extensive shear banding. On the other hand, no shear banding was observed for AgCu-E alloy at similar microstructural refinement. At higher strains deformation induced intermixing of Ag and Cu atoms was observed. Further, three-dimensional diffraction analysis of AgCu-E alloy showed that in contrast to conventional single phase alloys, the Ag and Cu phases develop similar crystallographic texture.